THE EFFECT OF BREATHING ENGINEERING ON CHANGES IN THE LEVEL OF ANXIETY IN THE MOM IN THE TIME OF LABOR AT THE AEK GOTI PUSKESMAS, SILANGKITANG DISTRICT, LABUSEL REGENCY IN 2021 - Niasty Lasmy Zaen (Science Midwifery, 2022)
Maternity feels anxious and afraid to face the labor process, then the adrenaline hormone will come out and can inhibit the release of oxytocin which is needed for the progress of labor. The purpose of deep breathing relaxation is so that individuals can control themselves when there is a feeling of tension and stress that makes individuals feel in an uncomfortable condition to be comfortable, the purpose of the study is to find out whether there is an effect of deep breathing techniques on the level of anxiety in the first stage of labor at the Aek Goti Public Health Center. district. Silangkitang, Labusel Regency in 2021. This study uses a quantitative research type, the population used is all patients who delivered the first stage of labor at the Aek Goti Public Health Center, Silangkitang district, Labusel Regency which was carried out in August 2021 with a population of 25 mothers during the first stage of labor. sampling technique at the time of the study. Data analysis used Wilcoxon Signed Rank Test. The results of this study were the level of anxiety in the first stage of labor before giving the method of deep breathing relaxation techniques at the Aek Goti Health Center, Kec. Silangkitang Labusel Regency in 2021 the majority experienced severe anxiety as many as 11 respondents. The level of anxiety in the first stage of labor after giving the method of deep breathing relaxation techniques at the Aek Goti Health Center, Silangkitang District, Labusel Regency in 2021, the majority experienced moderate anxiety as many as 12 respondents. Conclusion These results prove that there is a significant effect of deep breathing techniques on the level of anxiety in the first stage of labor at the Aek Goti Health Center, Silangkitang District, Labusel Regency in 2021. These results prove that deep breathing techniques can reduce the level of anxiety in the first stage of labor. It is recommended that midwives are able to be directly involved in the process of deep breathing relaxation techniques so that the implementation of relaxation techniques can be carried out optimally by patients.